Bone Regeneration By Orthodontic Tooth Movement - Defne Çaldemir; Sönmez Fıratlı (Turkish Journal of Orthodontics, 2012)

(untitled)
This case report describes the creation of appropriate alveolar bone level by orthodontic tooth movement in a 43-year-old man with inappropriate alveolar bone level at an edentulous site, which prevented the placement of an implant necessary for prosthetic restoration.